1999
DOI: 10.1038/sj.bjc.6690107
|View full text |Cite
|
Sign up to set email alerts
|

Faecal occult blood screening and reduction of colorectal cancer mortality: a case-control study

Abstract: SummaryTo estimate the efficacy of screening on colorectal cancer mortality, a population-based case-control study was conducted in welldefined areas of Burgundy (France). Screening by faecal occult blood test prior to diagnosis in cases born between 1914 and 1943 and who died of colorectal cancer diagnosed in 1988-94 was compared with screening in controls matched with the case for age, sex and place of residence. Cases were less likely to have been screened than controls, with an odds ratio (OR) of 0.67 [95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 14 publications
2
17
1
3
Order By: Relevance
“…Reports on rates of re-participation in the literature are scarce and inconsistent, and vary depending on country and whether the data comes from randomised controlled trials, feasibility studies or full programs (Jansen, 1984;Kewenter et al, 1988;Hardcastle et al, 1996;Hart et al, 1997;Faivre et al, 1999;Mandel et al, 1999;Jorgenson et al, 2002;Weller et al, 2007;Lindholm et al, 2008;Steele et al, 2009). Some studies failed to invite firstround non-participants in subsequent rounds (Kronborg et al, 1989) although our results show that this would be unwise in organised programs because such people may become Late Entrants.…”
Section: Discussioncontrasting
confidence: 48%
“…Reports on rates of re-participation in the literature are scarce and inconsistent, and vary depending on country and whether the data comes from randomised controlled trials, feasibility studies or full programs (Jansen, 1984;Kewenter et al, 1988;Hardcastle et al, 1996;Hart et al, 1997;Faivre et al, 1999;Mandel et al, 1999;Jorgenson et al, 2002;Weller et al, 2007;Lindholm et al, 2008;Steele et al, 2009). Some studies failed to invite firstround non-participants in subsequent rounds (Kronborg et al, 1989) although our results show that this would be unwise in organised programs because such people may become Late Entrants.…”
Section: Discussioncontrasting
confidence: 48%
“…Three other large trials have now been undertaken using unrehydrated tests and two have reported a more modest but highly significant 15%-20% population mortality reduction [21,22] . A recent French case-control study is also consistent with these results [23] .…”
Section: Colorectal Cancersupporting
confidence: 78%
“…[5][6][7][8][9][10][11] In one of the randomised studies a reduction in the incidence of CRC has been found. 12 For these reasons FOBT has been recommended as a screening tool for CRC [13][14][15] and several national population based screening programmes have been or are being started worldwide.…”
mentioning
confidence: 99%